Radix spp.: Identification of trematode intermediate hosts in the Czech Republic - Huňová, Kateřina; Kašný, Martin; Hampl, Vladimír; Leontovyč, Roman; Kuběna, Aleš; Mikeš, Libor; Horák, Petr (Acta parasitologica, 2012)
Lymnaeid snails of the genus Radix serve as intermediate hosts of some schistosomes and fasciolids. In Europe, delineation of species within the genus Radix is unresolved and, therefore, spectrum of snail hosts susceptible to trematode infections is under discussion. We used and compared three criteria for species delineation using snails collected at 43 localities. (a) Sequence analysis of ITS-2 rDNA disclosed that the collected snails belong to four species - R. auricularia (Linnaeus, 1758), R. peregra (Müller, 1774), R. lagotis (Schrank, 1803) and R. labiata (Rossmaessler, 1835) (criteria and names are based on the work of Bargues et al. 2001). Occurrence of R. peregra in the Czech Republic was confirmed by molecular data for the first time. (b) Characterization of reproductive system disclosed differences in location, size and shape of bursa copulatrix and its ductus. Unfortunately, some R. labiata specimens shared morphological features of reproductive organs with R. lagotis. (c) Statistical analysis of shell morphology proved that significant differences exist among particular species. One prediction model showed that correct classification of species may be achieved in 82-84% of cases. However, identification of individual snails in the field (without knowledge of respective snail population and use of statistical tools) still remains a complicated issue due to overlaps of shell characteristics. Concerning the role in trematode transmission, R. lagotis, R. labiata and R. peregra are susceptible to Trichobilharzia regenti. Also, successful experimental infections of R. lagotis and R. labiata by Fascioloides magna were accomplished.
Keywords: Česká republika; Snails; Czech Republic; druhová specificita; Disease Reservoirs; Animals; Species Specificity; hlemýždi; zdroje nemoci; Host-Parasite Interactions; zvířata; interakce hostitele a parazita; Trematoda